The study of relation between the gestational age of human fetuses and the diaphyseal length of humerus using ultrasonography - B R Chaithra Rao; Sunkeswari Sreepadma; R N Kalghatgi (Wolters Kluwer Medknow Publications, 2017)
Background and Objectives: Ultrasonography is the most effective way to date pregnancy and to estimate the fetal weight in obstetric clinics. Currently, the diaphyseal length of humerus is used as a new parameter to estimate gestational age. The study evaluates the diaphyseal length of humerus as a parameter to estimate the gestational age of the fetus at the time of examination and to assess the growth pattern of humerus with advancing gestational age. Methods: The study was done on 152 antenatal women aged between 20 to 30 years of gestational ages from 15 to 40 weeks from the district of Dharwad, Karnataka, Subjects with maternal disease known to affect normal fetal growth were excluded. The diaphyseal length of humerus was measured by radiologist in a standardized manner. The study describes the relationship of the diaphyseal length of humerus in centimeters, with the advancing gestational age in weeks. Results: It was observed that the diaphyseal length of humerus gradually increased from 15 weeks to 40 weeks of gestation and that the relationship is linear and direct. Normograms of diaphyseal lengths of humerus can be constructed by the formula derived by this study for this particular geographical area. Conclusion: The relationship between the diaphyseal length of humerus and the gestational age is linear and direct. The measurement of the diaphyseal lengths of humerus [in cm] can be an important additional parameter for estimating gestational age along with other parameters.